Entrance of the French into Vienna on 14 November 1805 - Pigeot, Françis, b. 1775 (engraver):::Creator::::::::::::; Le Compte (artist):::Contributor:::::::::::: (France; chez Bance aîné, Md. d'Estampes, Rue St. Denis; Paris)
Color engraving of the entrance of French troops into Vienna on November 14, 1805